Telehealth Trials to Address Health Equity in Stroke Survivors. Issue 2 (24th January 2023) - Sharrief, Anjail Z.; Guzik, Amy K.; Jones, Erica; Okpala, Munachi; Love, Mary F.; Ranasinghe, Tamra Ishan Jayenda; Bushnell, Cheryl
Abstract : Telehealth has seen rapid expansion into chronic care management in the past 3 years because of the COVID-19 pandemic. Telehealth for acute care management has expanded access to equitable stroke care to many patients over the past two decades, but there is limited evidence for its benefit for addressing disparities in the chronic care of patients living with stroke. In this review, we discuss advantages and disadvantages of telehealth use for the outpatient management of stroke survivors. Further, we explore opportunities and potential barriers for telehealth in addressing disparities in stroke outcomes related to various social determinants of health. We discuss two ongoing large randomized trials that are utilizing telehealth and telemonitoring for management of blood pressure in diverse patient populations. Finally, we discuss strategies to address barriers to telehealth use in patients with stroke and in populations with adverse social determinants of health.